Ipsilateral facial nerve injury with contralateral labyrinthine concussion and subdural hematoma in a case of longitudinal temporal bone fracture (Bangladesh Journal of Medical Science, 2017)
Head trauma can lead to hearing loss. Both sensorineural and conductive hearing loss has been reported in cases of head injury. We report a case of labyrinthine concussion and subdural hematoma in the opposite ear of a patient who had head trauma after involved in motor vehicle accident. A complete hearing assessment for head trauma patients should be advised as it can avoid misdiagnosis and negligence in management.Bangladesh Journal of Medical Science Vol.16(4) 2017 p.594-596